1986
DOI: 10.1051/lait:1986311
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation du lysozyme en tant qu'agent régulateur de l'affinage en fromagerie MMV

Abstract: RésuméL'évolution du pH, de la flore microbienne et de l'azote non protéique des fromages Camembert et Saint-Paulin issus de technologies classiques et MMV a été comparée au cours de leur affinage. Si aucune différence significative n'était mise en évidence pour ce qui est des fromages Camembert, il n'en était pas de même pour les fromages Saint-Paulin issus des deux technologies. Les fromages fabriqués à partir de lait ultrafiltré contenaient 10 fois plus de germes aérobies mésophiles ; leur pH restait plus é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…Both enumeration of viable cells of added starters and immunoblotting data related to intracellular enzyme markers con-firm that in cheeses made from milk concentrated by UF at milk pH, no lysis of Lactococcus starter was detected, as previously hypothesized by Goudédranche et al [12] and Mistry and Maubois [30]. Such a change in a phenomenon essential for the normal ripening of cheese can be related to the environmental conditions of Lactococcus in this type of UF-cheeses.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Both enumeration of viable cells of added starters and immunoblotting data related to intracellular enzyme markers con-firm that in cheeses made from milk concentrated by UF at milk pH, no lysis of Lactococcus starter was detected, as previously hypothesized by Goudédranche et al [12] and Mistry and Maubois [30]. Such a change in a phenomenon essential for the normal ripening of cheese can be related to the environmental conditions of Lactococcus in this type of UF-cheeses.…”
Section: Discussionsupporting
confidence: 75%
“…cremoris E8 alone in traditional Cheddar cheese. Goudédranche et al [12] improved the texture and the flavor of UF-Saint-Paulin and Camembert cheeses by adding 0.5 or 1.0 g . kg -1 of lysozyme to liquid pre-cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Promotion or inhibition of primary proteolysis will affect the development of bitterness in cheeses made from heated milk, but also curd fusion, ripening, and melting properties of the cheeses, based on yet debated mechanisms that do not always involve the heat-denatured whey proteins. UF concentration of cheese milk is eventually known to increase the buffering capacity of the cheese curd and to influence growth and lysis of the ripening microorganisms [55]. Its use in combination with heat-treatment to recover the whey proteins in cheese may generate effects on texture and flavour that are independent of properties of the denatured whey proteins.…”
Section: Quality Of Cheeses Made With Heated Milkmentioning
confidence: 99%
“…Many previous studies have reported that the ripening of cheeses made from ultrafiltered milk (UF-cheeses) is slower or delayed in comparison to cheeses manufactured by traditional methods [1,5,6,8,9,14,17,23]. These studies have reported that in UF-cheeses, the level of proteolysis is low in comparison to traditional cheeses and consequently the ripening of these cheeses is delayed.…”
Section: Introductionmentioning
confidence: 99%